Climate Contributions and the Paris Agreement: Fairness and Equity in a Bottom-Up Architecture. Issue 3 (12th September 2016) - Chan, Nicholas
Abstract : One of the chief aspects of last December's landmark Paris Agreement on climate change was the acceptance of the notion that all states would make a "contribution" to the global effort to address climate change. These voluntary, nationally determined, non-binding pledges are the most visible feature of the reorientation of the international climate regime away from its previous emphasis on "top-down" international coordination, and toward a "bottom-up" architecture that provides greater national flexibility in order to induce broader participation. At the same time, however, the agreement to keep the rise in average global temperatures to below 2 degrees Celsius indicates that there is a limit to the quantity of carbon that can be emitted to meet this temperature goal, raising the challenge of how to apportion this carbon "budget" among states. Can a fair distribution of the carbon budget be achieved amid voluntary contributions? This paper first discusses the tension between the top-down distribution that a carbon budget approach generally implies, and the bottom-up institutional elements of the new climate architecture. Second, it reviews the alternative ways in which considerations of fairness have been integrated into the design of the Paris Agreement, and the rise of "national circumstances" as the context for fairness. Finally, this paper points to the increased role for normative argumentation in this bottom-up world, where new norms embedded in the Paris Agreement, especially relating to increases in national ambition, take on greater importance in efforts to achieve an equitable response to climate change.